Mitochondrial Diversity in Human Head Louse Populations Across the Americas - Ascunce, Marina S. (2013)
Anthropological studies suggest that the genetic makeup of human populations in the Americas is the result of diverse processes including the initial colonization of the continent by the first people plus post-1492 European migrations. Because of the recent nature of some of these events, understanding the geographical origin of American human diversity is challenging. However, human parasites have faster evolutionary rates and larger population sizes allowing them to maintain greater levels of genetic diversity than their hosts. Thus, we can use human parasites to provide insights into some aspects of human evolution that may be unclear from direct evidence. In this study, we analyzed mitochondrial DNA (mtDNA) sequences from 450 head lice in the Americas. Haplotypes clustered into two well-supported haplogroups, known as A and B. Haplogroup frequencies differ significantly among North, Central and South America. Within each haplogroup, we found evidence of demographic expansions around 16,000 and 20,000 years ago, which correspond broadly with those estimated for Native Americans. The parallel timing of demographic expansions of human lice and Native Americans plus the contrasting pattern between the distribution of haplogroups A and B through the Americas suggests that human lice can provide additional evidence about the human colonization of the New World.